2016
DOI: 10.1161/hypertensionaha.116.07548
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Blockade of the Androgen Receptor Abolishes Age-Dependent Increases in Blood Pressure in Female Growth-Restricted Rats

Abstract: Intrauterine growth restriction induced via placental insufficiency programs a significant increase in blood pressure at 12 months of age in female growth-restricted rats that is associated with early cessation of estrous cyclicity indicative of premature reproductive senescence. In addition, female growth-restricted rats at 12 months of age exhibit a significant increase in circulating testosterone with no change in circulating estradiol. Testosterone is positively associated with blood pressure after menopau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 70 publications
(88 reference statements)
3
30
0
Order By: Relevance
“…Testosterone is implicated in the activation of the RAS in the aging female spontaneously hypertensive rat (42). Thus, Dasinger and colleagues also demonstrated that intramedullary expression of the angiotensin type 1 receptor was increased in untreated female IUGR offspring at one year of age, but did not differ in female IUGR treated with flutamide relative to untreated female controls (41). Based on these findings, Dasinger and colleagues proposed that testosterone-mediated activation of the RAS contributes to the development of increased blood pressure in female IUGR offspring at one year of age (Figure).…”
Section: Sex Steroids the Renin Angiotensin System And The Developmmentioning
confidence: 95%
See 3 more Smart Citations
“…Testosterone is implicated in the activation of the RAS in the aging female spontaneously hypertensive rat (42). Thus, Dasinger and colleagues also demonstrated that intramedullary expression of the angiotensin type 1 receptor was increased in untreated female IUGR offspring at one year of age, but did not differ in female IUGR treated with flutamide relative to untreated female controls (41). Based on these findings, Dasinger and colleagues proposed that testosterone-mediated activation of the RAS contributes to the development of increased blood pressure in female IUGR offspring at one year of age (Figure).…”
Section: Sex Steroids the Renin Angiotensin System And The Developmmentioning
confidence: 95%
“…To address the hypothesis that an increase in testosterone contributes to the pathogenesis of elevated blood pressure in female IUGR offspring at one year of age, a recent study published in Hypertension showed that chronic blockade of the androgen receptor with flutamide abolished the significant increase in blood pressure at one year of age in female IUGR rat offspring programmed by fetal exposure to placental insufficiency (41). In this study by Dasinger et al, chronic treatment with enalapril also decreased blood pressure in female IUGR offspring indicating a role for the RAS (41). Testosterone is implicated in the activation of the RAS in the aging female spontaneously hypertensive rat (42).…”
Section: Sex Steroids the Renin Angiotensin System And The Developmmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous mechanisms contribute to sex differences in primary hypertension with a role for sex steroids implicated in the progression of CV risk (11. Sex steroids may also contribute to sex differences in the onset of increased blood pressure that has its origins in fetal life (12). …”
Section: Introductionmentioning
confidence: 99%